2001
DOI: 10.1073/pnas.051625398
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying losses of heterozygosity in human colorectal cancers

Abstract: Losses of heterozygosity are the most common molecular genetic alteration observed in human cancers. However, there have been few systematic studies to understand the mechanism(s) responsible for losses of heterozygosity in such tumors. Here we report a detailed investigation of the five chromosomes lost most frequently in human colorectal cancers. A total of 10,216 determinations were made with 88 microsatellite markers, revealing 245 chromosomal loss events. The mechanisms of loss were remarkably chromosome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 47 publications
7
133
1
Order By: Relevance
“…The gain or loss of an entire chromosome arm rather than of a small segment is thus a favored mechanism, and possibly represents one of the earliest events in CIN. A study that combined karyotyping and marker analysis showed that individual chromosome arms could be gained in near-diploid cells, 47 which suggests that no polyploid intermediate would be necessary to start the BFB cycle in cancer. Instead, and in agreement with the initial experiments in maize, 25 gaining a single "reactive" chromosome arm is enough Figure 1.…”
Section: Back To Bfbmentioning
confidence: 99%
See 1 more Smart Citation
“…The gain or loss of an entire chromosome arm rather than of a small segment is thus a favored mechanism, and possibly represents one of the earliest events in CIN. A study that combined karyotyping and marker analysis showed that individual chromosome arms could be gained in near-diploid cells, 47 which suggests that no polyploid intermediate would be necessary to start the BFB cycle in cancer. Instead, and in agreement with the initial experiments in maize, 25 gaining a single "reactive" chromosome arm is enough Figure 1.…”
Section: Back To Bfbmentioning
confidence: 99%
“…Although it is unlikely that spindle-induced rupture is selective for a specific centromere, not all chromosome arms undergo changes at the same rate; in many cases, one chromosome arm is lost while the other is preserved or amplified. 47 Arms that contain oncogenes such as c-Myc (8q), ErbB2 (17q) or Pik3CA (3q) are amplified much more often than average. 33 Even though mitotic centromere rupture and gain of chromosome arms are random events, oncogenes located on amplified arms thus seem to offer a selective growth advantage.…”
Section: Evidence From Tumorsmentioning
confidence: 99%
“…In some cases, the deviation from 50%:50% is dependent on the parent of origin, such as genomic imprinting (Reik and Walter, 2001;Barlow, 2011;Bartolomei and Ferguson-Smith, 2011) and imprinted X chromosome inactivation (Wake et al, 1976;Huynh and Lee, 2001;Xue et al, 2002;Dindot et al, 2004;Wang et al, 2013a). In other cases, the AI is random or sequence dependent, such as random X chromosome inactivation (Heard et al, 1997), autosomal random monoallelic expression (RMAE; Gimelbrant et al, 2007), allelic exclusion of immunoglobulin genes (Vettermann and Schlissel, 2010), cis-regulating expression quantitative trait loci (cis-eQTL), loss of heterozygosity in cancer (Thiagalingam et al, 2001) and monoallelic expression of olfactory receptors (Chess et al, 1994). Technical details of the methods for quantifying differential allelic expression (DAE) accurately are critical to study AI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LOH of chromosome 5q is correlated with biallelic inactivation of the tumor suppressor gene, adenomatous polyposis coli (APC), a process that occurs early in the multistep colorectal carcinogenesis (Fearon and Vogelstein, 1990). Other frequently observed LOH in CRC involves chromosomes 1p, 8p, 17p and 18q (Thiagalingam et al, 2001).…”
Section: Introductionmentioning
confidence: 99%